Gesellschaft der Freunde der Kunstsammlung Nordrhein-Westfalen. - Kunstsammlung Nordrhein-Westfalen, Düsseldorf (Düsseldorf : Gesellschaft der Freunde der Kunstsammlung Nordrhein-Westfalen, 1987)
Modigliani, Amedeo ; Bacon, Francis ; Nicholson, Ben ; Francis, Sam ; Johns, Jasper ; Fontana, Lucio ; Arman ; Klapheck, Konrad ; Uecker, Günther ; Antes, Horst
Duits
boek